Journalism, Digital Media and the Fourth Industrial Revolution - Sixto-García, José; Quian, Alberto; Rodríguez-Vázquez, Ana-Isabel; Silva-Rodríguez, Alba; Soengas-Pérez, Xosé (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
XXIII, 274 p.